In vitro skin penetration of petrolatum and soybean oil and effects of glyceryl monooleate. (15th August 2018) - Intarakumhaeng, R.; Shi, Z.; Wanasathop, A.; Stella, Q. C.; Wei, K. S.; Styczynski, P. B.; Li, C.; Smith, E. D.; Li, S. K.
Abstract : Objectives: Petrolatum and soybean oil are common ingredients incorporated in topical skin formulations for skin protection and moisturization. However, the stratum corneum (SC) penetration kinetics of these two cosmetic ingredients has not been systematically studied. Glyceryl monooleate (GlyMOle) has been shown to enhance skin penetration of various compounds. It was hypothesized that GlyMOle could enhance skin penetration of petrolatum and soybean oil. This study aimed to examine the in vitro skin penetration of petrolatum and soybean oil in the presence or absence of GlyMOle. Methods: Skin permeation experiments were conducted using the in vitro Franz diffusion cell model with split‐thickness human skin and human epidermal membrane (HEM). The effect of permeant dose and the kinetics of permeant penetration were examined with and without GlyMOle in vitro . Results: Petrolatum and soybean oil were found to permeate across HEM, and no effect of GlyMOle on skin permeation into the receptor chamber was observed. GlyMOle enhanced the penetration of petrolatum into the split‐thickness skin at 50 μ g dose (petrolatum:GlyMOle, 49 : 1, w/w). However, no effect of GlyMOle on petrolatum penetration was observed at 200 μ g dose (of the same petrolatum:GlyMOle ratio), indicating a dose‐dependent effect. GlyMOle at the level used in the study did not enhance the penetration of soybean oil with 50 and 200 μ g doses at any timepoints. Conclusion: GlyMOle was a skin penetration enhancer for petrolatum under the in vitro conditions identified in this study.